Exploration of Creative Thinking Skills of Students in Physics Learning - Muhammad Asriadi; Edi Istiyono (Universitas Negeri Makassar, 2020)
This study aims to determine the ability of creative thinking high school students in physics learning, know the form of assessment of creative thinking abilities. The study was conducted at SMAN 6 Yogyakrata. This type of research is a survey with a cross-sectional method that is a survey conducted once and at a time. The subjects were the principals, teachers of physics from SMAN 6 Yogyakrata and 30 grade XI students. observations, interviews, and questionnaires were used as data collection techniques. The data analysis method used was the quantitative-qualitative descriptive analysis. The results showed that the creative thinking ability of class XI MIA 1 students at SMAN 6 Yogyakarta can be said to be in the average and quite good category, although there are some students whose level of creative thinking ability is low. In addition, the form of assessment used by physics teachers has not been effective and accurate enough in assessing students 'creative thinking abilities. So it is recommended to use The Torrance Tests of Creative Thinking (TTCT) in physics learning because it has been proven to be accurate in assessing students' creative thinking abilities.